B. Frishmuth and T. Bernhard: Autobiographical Prose - L. V. Trofimova (Научный диалог, 2018)
The article is devoted to the autobiographical prose of Austrian writers Barbara Frishmuth and Thomas Bernhard. The material used were works by B. Frishmuth “Monastery School” and T. Bernhard “Cause”, in which the features of the “biographical author” are clearly seen. The research is conducted in a comparative aspect. It is reported that in these works devoted to the problem of the keeping girls and boys in boarding schools, the issue of the interaction of religion and the school in the education of children in postwar Austria is raised. Particular attention is paid to the fact that both authors have experience of staying out of the family: the life of B. Bernstein is described in bright colors, and Bernhard’s autobiographical prose hopelessness is seen. The selected perspective of the study takes into account women's approach to dealing with problems in the work of Barbara Frishmuth. The relevance of the study is stipulated by the interest of modern Russian literary studies to the trends of development of German-language literature of the XX century, insufficient study of the work of the Austrian writer B. Frishmuth in the domestic literary criticism and lack of a comparative analysis of the autobiographical works of two outstanding representatives of Austrian literature. It is shown that the comparison of the two works may be a part of a more close study of the dialogue between B. Frishmuth and T. Bernhard.